Child development - Santrock, John W. (New York McGraw-Hill Education, 2024)
"This edition of Child Development has focused on providing a systematic, integrative approach that helps students make connections in their learning and practice"
Section 1. The nature of child development -- Section 2. Biological processes, physical development, and perceptual development -- Section 3. Cognition and language -- Section 4. Socioemotional development -- Section 5. Social Systems in Development.
Includes bibliographical references (pages R1-R65) and index.
Keywords: Child development; Child psychology